Художня репрезентація жіночості в сучасній українській романістиці - Башкирова, О. (Слово і Час, 2020)
Статтю присвячено провідним тенденціям художньої рецепції жіночих образів у сучасній українській романістиці. Принципи моделювання жіночості в літературі розглянуто з позицій гендерних студій,
постколоніальної та психоаналітичної теорій. На численних прикладах продемонстровано основні вектори художнього переосмислення
типових для національної літературної традиції жіночих образів:
матері, хранительки роду, демонічної жінки. Описано альтернативні типи фемінної ідентичності, репрезентовані культурологічним та
феміністичним жіночим письмом. На основі масштабних узагальнень
художньої практики останніх десятиліть визначено провідні світоглядні інтенції сучасної романістики, передусім прагнення до гендерного паритету, повноцінного діалогу чоловіків і жінок як рівноправних суб'єктів культуротворення. The paper deals with the main tendencies of the artistic reception of women images in modern
Ukrainian novels. The principles of modeling femininity in literature have been considered
from the positions of the gender studies, postcolonial and psychoanalytic theory. It is
proved that the peculiarities of this modeling are determined by stylistic and genre tendencies
of the Ukrainian literature. The interpretation of feminine images typical for the national
literary tradition (mother, family-keeper, demonic woman) has been demonstrated in
numerous examples. These images correlate with the fundamental artistic principles of the
turning points in history (actualization of the archetypes, attention to the irrational manifestations
of human psychics). They display the ‘masculine’ literary tradition (representation
of a woman as an external object), but at the same time demonstrate a new accent in the
understanding of the gender roles (woman as a mentor of a man). The alternative types of
the feminine identity represented by feminist and culturological women’s writing have been
explored as well. Special attention has been paid to procreation as the main woman’s ability,
which forms different models of feminine mentality — from the essentialist mother-type to
the image of a child-free woman. The modeling of a feminine artistic worldview becomes an
actual strategy in overcoming the postcolonial trauma. It is explained by the peculiarities of
the postcolonial literatures, which fulfill their historical reflections in the local family stories.
In this context, feminine conscience gets the status of a memory-keeper and shows the
ability to trace the development of national history in its everyday dimensions. Based on the
large-scale generalization of the last decades’ artistic practice, the researcher determines the
main worldview intentions of modern novels, in particular the tendency to achieve gender
parity, the full-fledged dialogue of men and women as the equal subjects of culture creation.